Pengaruh Kompetensi, Zona Kerja Fisik dan Ketaatan Kerja terhadap Perfoma Karyawan melalui Kepuasan Kerja sebagai Intervensi - Purnawiyanto, Hari; Indarto, Indarto; Saddewisasi, Wyati (IPM2KPE, 2024)
This study aims to analyze the influence of competence, physical work zone, and work compliance on employee performance with job satisfaction as an intervening variable, with a case study at PT Pertamina Marine Solutions in the Semarang and Cilacap areas. This study uses a quantitative approach with a survey method implemented through the distribution of questionnaires. The population in this study were all TKJP employees of PT Pertamina Marine Solutions, and samples were taken randomly with 107 respondents. Validity and reliability tests were carried out on the questionnaires used. Data analysis was carried out using descriptive analysis and Structural Equation Modeling (SEM) with hypothesis testing and intervening tests assisted by the Smart PLS 4.0 program. The results of the study indicate that competence has a positive and significant influence on employee job satisfaction and performance. In addition, job satisfaction has been proven to be able to mediate the influence of competence and work compliance on employee performance. Thus, the higher the competence and work compliance of employees, the better their performance level, especially if supported by an optimal level of job satisfaction. Keywords: Competence, Work Compliance, Job Satisfaction, Employee Performance, Physical Work Zone